2010
DOI: 10.1177/0272431610384486
|View full text |Cite
|
Sign up to set email alerts
|

Injunctive and Descriptive Peer Group Norms and the Academic Adjustment of Rural Early Adolescents

Abstract: This study integrates diverse literatures on peer group influence by conceptualizing and examining the relationship of peer group injunctive norms to the academic adjustment of a large and ethnically diverse sample of rural early adolescents' academic adjustment. Results of three-level hierarchical linear modeling indicated that peer groups were differentiated by injunctive norms for effort and achievement. After accounting for prior adjustment, peer group injunctive norms predicted changes to students' school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…Ryan (2001) also found no differences by ethnicity in relationships among students' motivation and achievement and their peer group affiliations. Other researchers have also reported a lack of difference between ethnic minority and White students in the relationship between structural and normative features of peer groups and their subsequent adjustment (Hamm, Schmid et al, 2011;Wilson et al, 2011). Given the potential for, and limited attention to group differences by gender and ethnicity, we examined differences in the relationship of these aspects of social integration to students' perceptions of their transition experience by both students' gender and ethnic minority status.…”
Section: The Current Studymentioning
confidence: 95%
See 4 more Smart Citations
“…Ryan (2001) also found no differences by ethnicity in relationships among students' motivation and achievement and their peer group affiliations. Other researchers have also reported a lack of difference between ethnic minority and White students in the relationship between structural and normative features of peer groups and their subsequent adjustment (Hamm, Schmid et al, 2011;Wilson et al, 2011). Given the potential for, and limited attention to group differences by gender and ethnicity, we examined differences in the relationship of these aspects of social integration to students' perceptions of their transition experience by both students' gender and ethnic minority status.…”
Section: The Current Studymentioning
confidence: 95%
“…Research on peer relationships at the transition suggests that girls showed greater instability in their peer affiliations as compared to boys (Hardy et al, 2002), but boys and girls have not been found to differ in peer acceptance at the middle school transition (Hardy et al, 2002;Kingery et al, 2011). Gender differences have not been found in the structural and normative features of boys' and girls' peer groups following the transition to middle school (Ellis & Zarbatany, 2007;Hamm, Schmid et al, 2011;Wilson et al, 2011).…”
Section: The Current Studymentioning
confidence: 98%
See 3 more Smart Citations